A Generalization of Prešić Type Mappings in Metric-Like Spaces. (22nd April 2013) - Shukla, Satish; Fisher, Brian
Abstract : We generalize the result of Prešić in metric-like spaces by proving some common fixed point theorems for Prešić type mappings in metric-like spaces. An example is given which shows that the generalization is proper.